Study the anti-microbial growth properties of knitted cotton fabrics that’s treatment with Nano-Zno nanoparticles (Damascus University Journal for engineering sciences, 2021)
In this work. The development of antimicrobial Knitted cotton fabrics, which is widely used in underwear and socks, using Zinc oxide nanoparticles has been investigated. The nano-ZnO particles were prepared by wet chemical method and were directly applied on to the 100% knitted cotton fabric.Agar dishes were used as a microbial feeder with incubator, Staphylococcus aurues, Escherichia coli, Binder, Zinc ZnCl2 (purity 98%). And was applied to fabric prepared for the manufacture of socks. The results show that the finished fabric demonstrated significant antibacterial activity against: S. aureus in both qualitative and quantitative tests, According to the possibilities available for this research.It was found that when the treatment time increased the weight of the fabric decreased, and the antibacterial activity decreased. On the other hand, the increased of the Nano-ZnO amount didn’t affect the antibacterial activity, and the fabric weight.
Keywords: : Knitted cotton fabrics; Nano-Zno; Nano particles; Anti-microbial growth